A Retrospective Comparison of Trabeculectomy, Baerveldt Glaucoma Implant, and Microinvasive Glaucoma Surgeries in a Three-Year Follow-Up. (17th November 2021) - Nuzzi, Raffaele; Gremmo, Giulia; Toja, Francesca; Marolo, Paola
ABSTRACT: Purpose : This retrospective study aimed to evaluate the safety and efficacy of MIGS (Xen® and Cypass®) compared to trabeculectomy and Baerveldt® implants. Patients and Methods: This single-center study included patients from the Ophthalmic Hospital of Turin between January 2015 and 2018. Efficacy was assessed based on the intraocular pressure and the number of medications necessary to control IOP at 1, 3, 6, 12, 24, and 36 months and the potential complications. Complete surgical success was defined as IOP ≤ 21 mmHg, with no medication or additional glaucoma surgery. Qualified success was defined as IOP ≤ 21 mmHg with the reintroduction of topical medications. Our third measure of success was a delta IOP reduction greater than 20% compared to baseline. Results: The delta IOP compared to the baseline was significant at every instance, except in the Xen® implant group. The average IOP distribution at different time points was significant, except at 1 and 12 months. The delta of the medication number compared to the baseline was significant at every instant. All three methods of success were analyzed using a Kaplan-Meier survival curve that identified a significant difference on the success rates of Xen®-trabeculectomy, Xen®-Baerveldt®, and Cypass®-Baerveldt®. Conclusion: MIGS can reduce the number of medication classes, thus increasing patient compliance and reducing topical ocular toxicity and general costs. Trabeculectomy remains the most effective option but still presents a percentage of failures that might increase during follow-up.